When I'm gone / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2023)
When I'm gone, I won't come back again I know it's like blood stop running through your vein I know it's like your consciousness has gone and you would faint I know it's like the sun starts hiding and it's going to rain And I know it's like the world is no longer beautiful but dull and plain But time can heal your pain And you'll be happy again As long as you don't go down memory lane As long as you keep me out of your brain And throw everything of me into the drain Never let your days be filled with dismay The memories will fade away The feelings will slowly die and decay When comes the day I'll be gone and walk away I will have no words to say but a thin smile to display I'm not gold for you to keep As I've been treated like something cheap Life must go on, that's ail I wanna say So never let your heart stray Looking for fragments of old memories